MEMBANGUN MINAT BELAJAR MELALUI PROGRAM BANTUAN SISWA MISKIN DI SMP NEGERI 1 SIMPANG EMPAT KABUPATEN ASAHAN - Amrizal, Dedi; Yusriati, Yusriati; Perlaya, Ardika (Scenario (Seminar of Social Sciences Engineering and Humaniora), 2021)
The government provides a Poor Student Assistance (BSM) program to meet the personal needs of students, so that students from poor families can continue their education. The BSM program funds must be used to increase students' interest in learning so that they can continue their education to a higher level. The purpose of this study was to determine how the efforts of schools and parents in building interest in learning through BSM at SMP Negeri 1 Simpang Empat, Asahan Regency. The research method used is descriptive method with a correlational approach and data collection techniques using quantitative. Based on the results of the research conducted, the implementation of the BSM program had an influence on student interest in learning at SMP Negeri 1 Simpang Empat, Asahan Regency.